Competitive advantages and barriers in international construction: an origin-host market approach - Lozano-Torró, Alicia; García-Segura, Tatiana; Montalbán-Domingo, Laura; Pellicer, Eugenio (Journal of Civil Engineering and Management, 2020)
The growing importance of international construction activity forces companies to find out what competitive advantages to provide and barriers to overcome to achieve success, considering the particular characteristics of their origin and destination countries. Seventy six articles regarding success in the international construction market in the period 2008–2017 are reviewed to identify the barriers and the competitive advantages that most affect the international success of contractors. The Chi-Square (χ²) statistical test is used to verify the influence of the origin and destination countries on these variables. The literature identifies the provision of trained human resources as the most important competitive advantage and cultural differences and political risks as the main barriers. The Chi-Square (χ²) test indicates a dependency relationship between the origin country and the competitive advantage “managerial ability” to achieve international success, and between the external barriers “link between countries”, “political environment” and “economic environment” with the target market. Results of this paper provide valuable information for any construction company seeking international success.